Corporate social responsibility (The library of corporate responsibilities, 2009)
The essays in this volume examine the emergence of the concept of corporate social responsibility and the use and uses that have been made of the language of corporate responsibility to explore the business/society relationship, or what might be described as the role of the modern corporation in contemporary society.